Interleukins 1-beta, -8, and histamine increases in highly trained, exercising athletes - Mucci, P.; Durand, F.; Lebel, B.; Bousquet, J.; Prefaut, C. (Medicine & Science in Sports & Exercise, 2000)
Purpose: Exercise-induced hypoxemia (EIH) in highly trained athletes is associated with an increase in histamine release (%H) during exercise. Certain cytokines, known as histamine-releasing factors, are capable of interacting with basophils and/or mast cells to cause the release of histamine. The aim of this study was to determine whether the increased histamine release in highly trained athletes is related to a high plasma level in interleukin-1 beta (IL-1[beta]), IL-3, or IL-8 in arterial blood. Methods: These parameters were measured in 11 endurance athletes (23.2 ± 1.2 yr (mean ± SEM)) known to develop exercise-induced hypoxemia and 11 control subjects (25.0 ± 1.1 yr) at rest, during an incremental exhaustive exercise test, and at the fifth minute of recovery. Results: Histamine release increased between rest and maximal exercise in the athletes (P < 0.01), showing a strong correlation with EIH (r = 0.76, P < 0.01) and was unchanged in the controls. IL-3 plasma concentration was not altered with training and/or with exercise. Circulating IL-8 levels were not different between trained and untrained subjects at any testing level and increased at maximal exercise in both groups (P < 0.01). IL-1[beta] plasma levels were higher in athletes than in controls (P < 0.05) at each testing level and increased during exercise only in the athletes (P < 0.05). Conclusion: An elevated concentration of IL-1[beta] in plasma and its association with increased IL-8 levels during exercise may partly explain the increase in %H associated with EIH in highly trained athletes. Histamine, IL-8, and IL-1[beta] releases during exercise reflect an inflammatory reaction, which is probably involved in EIH